Strengthening MSME Marketing based on Cultural Festival - Imanita Septian Rusdianti; Diah Yulisetiarini; Haifa Haifa (TGO Journal of Community Development, 2026)
The purpose of this activity is to strengthen MSMEs in Balung Lor Village, Jember through collaboration with cultural festivals as a strategy for local economic development as well as the preservation of traditions. The method used is Focus Group Discussion to explore the needs and challenges of business actors, as well as participatory observation in cultural festivals as a medium for promoting local products. Data analysis was carried out with a qualitative approach, resulting in a deep understanding of the perceptions of association chairs, academics, local communities, and MSME actors. The results of the study show that this activity is able to open new market access, increase the selling value of products, strengthen community networks, and foster community pride in village cultural identity. The discussion emphasized that cultural integration and MSMEs are not just promotions, but holistic strategies that are sustainable, relevant to previous research, and able to create a double impact, namely strengthening the local economy while preserving cultural heritage.